Biohazards of Vibrio cholerae and Vibrio parahaemolyticus in freshwater fish and their decontamination in Selangor markets, Malaysia - Ahmad, Noorlis (2012)
Bacteria of the genus Vibrio are capable of causing epidemics of cholera and human intestinal diseases. However, little is known on the biosafety level of Vibrio spp. in freshwater fish in Malaysia. The purpose of this study was to investigate the biohazard of Vibrio cholerae and Vibrio parahaemolyticus in freshwater fish at retail level in Malaysia. A combination technique of most probable number and polymerase chain reaction (MPN-PCR) method was used to quantify the prevalence and number of total Vibrio spp., pathogenic Vibrio cholerae harboring ctx genes and pathogenic Vibrio parahaemolyticus harboring tdh and trh genes, and to enumerate their density in the fish samples. The biohazard of vibrios was also carried out by phenotypic (antibiotic resistance) and genotypic (virulence genes detection and RAPDPCR) characterization of the isolates from freshwater fish. A kitchen simulation study was also conducted to provide decontamination and crosscontamination data and information for the estimation of the risk of acquiring vibriosis from consumption of freshwater fish and when handled in the local domestic kitchen. At retail level, 300 samples of two types of freshwater fish, Pangasius hypopthalmus (Catfish) and Oreochromis sp. (Red tilapia) normally available at the wet markets and hypermarkets were collected over a one year period (June 2009 to June 2010). The vibrios were isolated from the flesh, intestinal tracts and gills of the freshwater fish. By using MPN-PCR method, the prevalences of Vibrio spp., Vibrio cholerae, and Vibrio parahaemolyticus were found to be 100%, 2.67% and 25%, respectively. Vibrio cholerae (OmpW) was mostly detected from the gills of Red tilapia sampled in hypermarkets at 14% followed by 2% in Catfish intestinal tracts. All of the Vibrio cholerae isolates in this study were the non-01 and non-0139 Vibrio cholerae. However, Vibrio parahemolyticus (toxR) were detected in samples from both types of markets, 28% from Red tilapia gills followed by the intestinal tracts and flesh at 26%. Vibrio parahemolyticus was frequently found in Catfish gills (30%), followed by flesh (22%) and intestinal tract (18%). Using the MPN-PCR method, the occurrence of total Vibrio cholerae harboring ctx virulent genes were 0.67% and Vibrio parahemolyticus harboring tdh and trh were 4% and 0%, respectively. Even though, the detection of the virulent gene was relatively low but the concentration of total vibrios in the samples ranged from 3 X 104 MPN/g to 1.1X107 MPN/g. A total of 57 isolates (Vibrio cholerae = 8 isolates, Vibrio parahemolyticus = 49 isolates) were recovered by plating method and were confirmed by PCR. All of the isolates showed multi-resistance to as many as 15 antibiotics tested with high resistance to Bacitracin (98%), Furazolidone (88%) and Tetracycline (83%) and were mostly susceptible to Imipenem with only 11% showed resistance. The multiple antibiotic resistance (MAR) indices detected in the study, ranged from 0.13 to 0.93. RAPD-PCR was used to generate polymorphic genomic fingerprints to determine genetic relatedness among Vibrio cholerae and Vibrio parahaemolyticus isolates under study. Two primers (OPA10; 5’-GTGATCGCAG-3’ and OPAR8; 5’-TGGGGCTGTC-3’), out of the 10 primers used showed the best results and were selected for further study. It was found that all isolates of Vibrio cholerae and Vibrio parahaemolyticus could be grouped into two major clusters for each primer used. The clustering isolates based on RAPD-PCR profiles suggested that overall, most of the isolates were from both types of markets and clustered together into the same group although some isolates from other types of markets were also found clustered in the same group. A simulation study was conducted to imitate the real situation in domestic kitchens as much as possible to give a realistic quantitative data on how vibrios could be reduced by washing and soaking procedures. The eight procedures of washing and soaking were applied in this simulation study. It was found that the overall mean percent transfer rate for procedure 1 (without washing or soaking), procedure 2 (washed under running tap water), procedure 3 (soaked in 100 ml of sterile distilled water), procedure 4 (soaked in 100 ml of lime juice) and procedure 5 (soaked in 100 ml of tamarind juice) ranged from 0% to >100%, followed by procedure 6 (soaked in 1% NaCl solution) from 3.8% to > 100% and procedure 7 (soaked in 3% NaCl solution) from 80.6% to >100%. It was found that washing by rinsing and soaking the flesh of freshwater fish with tap and distilled water showed a 0 log reduction. By soaking the fish flesh in the lime juice, tamarind juice, 1%, 3% and 10% of NaCl solution could decrease the number of vibrios up to 2.9 log reduction.